Harnessing digital trade to advance the sustainable development goals: An empirical study - Anukoonwattaka; Witada; Pedro Romao; Nikita Shahu; Yann Duval (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2024)
Trade's profound digital transformation has spurred a new era of digital trade. However, little is known about the impact of digital trade and related policies on sustainable development. To investigate this, our exploratory study employs Fixed-Effects (FE) regressions, linking digital trade variables with all Sustainable Development Goals (SDGs) through SDG targets organized into 4 main areas of development: economic, social, environmental, and governance and global partnerships. Our findings point to a statistically significant and positive relationship between the advancement of SDG targets and the growth of digital trade, particularly in the social and environmental areas. The results related to economic development and governance and global partnerships present a more varied picture. Integrating digital trade policies into regional agreements could significantly enhance the prospects of achieving the SDGs but it remains critical to bridge the digital divide to leverage the full benefits of digital trade.
hdl:20.500.12870/6806
Keywords: F10; F13; Q01; 330; Sustainable development; SDGs; digital trade; digital trade policies; trade facilitation